THE EFFECT OF SYSTEM QUALITY ON THE USE OF HOSPITAL MANAGEMENT INFORMATION SYSTEMS AT THE 'AISYIYAH SITI FATIMAH HOSPITAL, SIDOARJO - Alfinda Ayu Hadikasari; Uce Indahyanti; Cholifah Cholifah; Umi Khoirun Nisak (Jurnal Penelitian, 2022)
Based on initial data obtained from Aisyiyah Siti Fatimah Hospital, Tulangan Sidoarjo, the use of SIMRS in the hospital is still not optimal, which is only 60% of the features provided. The purpose of this study was to analyze the influence of human resource factors and technological suitability on the utilization of hospital management information systems with a case study at the Hospital 'Aisyiyah Siti Fatimah Tulangan Sidoarjo. The type of research is quantitative research and the research design is causal associative research with the HOT Fit method approach. The data used is primary data by distributing questionnaires to SIMRS users. The sample size is 108 SIMRS users at the Hospital 'Aisyiyah Siti Fatimah Tulangan Sidoarjo. Samples were taken by simple random sampling with lottery technique and then recapitulation of data was then presented in the frequency tabulation table and tested by simple linear regression using SPSS.The results of the study using a simple linear regression test were the influence between the quality of the system and the use of the system on the hospital management information system at the Hospital 'Aisyiyah SIti Fatimah Tulangan Sidoarjo with a significance value (p) of 0.0001 then the value (p) 0.05 so that H0 is rejected, which means that there is a real or significant effect between system quality variables and system use.